Solutions manual for Recursive methods in economic dynamics - Irigoyen, Claudio (Harvard University Press, 2002)
This solutions manual is a companion volume to the classic textbook Recursive Methods in Economic Dynamics by Nancy L. Stokey and Robert E. Lucas. Efficient and lucid in approach, this manual will greatly enhance the value of Recursive Methods as a text for self-study.